Pendampingan Pembuatan Modul Ajar Berbasis KBC – Deep Learning - Alfaizah, Zakiyah; Husni, Muhammad (Irajagaddhita, 2025)
This mentoring activity aims to address the demands of 21st-century educational transformation through the integration of the Love-Based Curriculum (KBC) and the Deep Learning Approach (DL) in the development of teaching modules for MIS Mujahidin teachers. The main challenge for teachers today is designing learning experiences that go beyond content transfer, towards fostering deep understanding and holistic character. The KBC is promoted as a character framework focused on four pillars of fundamental values: Love for Self, Others, the Environment, and the Nation. These values serve as the soul of the curriculum, while the DL Approach serves as a pedagogical innovation that encourages conceptual understanding, personalized learning, and the use of technology to adapt teaching materials to students' unique profiles. The mentoring, held on November 10-12, 2025, in the MIS Mujahidin Teachers' Room, used the Workshop/Direct Practice method as the main focus, with the aim of equipping teachers in formulating Learning Objectives (TP) that incorporate KBC values and designing Learning Activity Flows that utilize DL strategies, such as project-based assignments and investigations. The results of the activity showed significant achievements: 100% of participating teachers successfully completed the initial draft of the Teaching Module that truly integrated KBC values in TP and deep learning strategies. This activity is a crucial first step towards the transformation of learning at MIS Mujahidin, with the long-term hope of realizing Personalized Learning and producing a Competitive Graduate Profile—who are not only cognitively superior, but also master 21st Century Skills (4C: Critical, Creative, Collaborative, Communication) and have a strong character based on the value of Love.